Microcontroller-Based Car Automatic Braking System - Hamid Nasrullah; Albert Kasman (Universitas Ibn Khaldun Bogor, 2023)
Traffic accidents are one of the largest causes of death in the world, with Indonesia being one of the countries that records a high death rate due to accidents. One of the main factors causing accidents is the driver's negligence in controlling the vehicle. In an effort to reduce accidents, automatic braking technology is an effective solution to prevent accidents due to braking system failure or the driver's inability to brake properly. The research aims to design and test an automatic braking system using an Arduino-based microcontroller and ultrasonic sensors to detect the distance of the obstacle in front of the vehicle. The system is designed to stop the vehicle automatically before it hits an obstacle, with testing conducted using the system's delay settings to optimise stopping distance. The test results showed that at a delay setting of 150 ms, the vehicle stopped at an average distance of 18.56 cm from the target of 20 cm, while at a delay setting of 300 ms, the vehicle stopped at an average distance of 25.44 cm from the target of 30 cm. This system shows a fairly high success rate in improving vehicle safety and reducing the risk of accidents.